The N-6 methyladenosine dynamics in STEMI and the effect of IL-6 inhibition - a hypothesis generating sub-study of the ASSAIL-MI trial - Dahl, Tuva B.; Quiles-Jiménez, Ana; Broch, Kaspar; Anstensrud, Anne Kristine; Gullestad, Lars; Andersen, Geir Ø.; Kleveland, Ola; Øgaard, Jonas; Bjerkeli, Vigdis; Rashidi, Azita; Yang, Kuan; Holven, Kirsten B.; et al. (Frontiers in Immunology, 2025)
BackgroundEpitranscriptomics, with m6A as the most prevalent in mammals, is a novel treatment target for inflammatory diseases, including cardiovascular diseases. However, little is known about m6A RNA-regulation during myocardial infarction (MI).MethodsIn this explorative sub-study of the ASSAIL-MI trial, we used whole blood samples from patients with acute ST-elevation MI (STEMI) (n=6) at admission and after 3–7 days, and from healthy control subjects (n=3). RNA was isolated, and m6A sites were analyzed using human m6A single nucleotide resolution microarray analysis. mRNA levels were analyzed using RNA sequencing analysis.ResultsCompared with controls, patients with STEMI had a strikingly different pattern of m6A deposition. In total, 845 m6A methylation sites in whole blood RNA were hypomethylated and 36 were hypermethylated compared with controls. Of the hypomethylated transcripts, 194 transcripts were lower expressed, while 197 transcripts were higher expressed. The m6A pattern changed from an overall hypomethylation at admission to an overall hypermethylation 3–7 day after admission. Anti-inflammatory treatment with tocilizumab further altered the m6A deposition.ConclusionsIn this hypothesis generating study, m6A deposition differs STEMI patients and healthy controls. The m6A pattern changes over the course of 3–7 days. This response is, at least to some degree, is modulated by blocking the IL-6 receptor. Our data may suggest that this post-transcriptional regulation of RNA is involved in the immune response during STEMI, highlighting its potential as a target for therapy in MI.